Positive Leukocyte Esterase Dipstick Test: Association With Spontaneous Bacterial Peritonitis In Patients Suffering From Liver Cirrhosis - Sumbul Shahzadi; Fuad Ahmad Siddiqi; Imran Khan; Kanaz Ahmad Siddiqi; Javed Ahmad Khan; Ayesha Ashraf Cheema (Journal of Rawalpindi Medical College)
Objective: To assess the diagnosing utility of the leukocyte esterase dipstick test by determining the association of a positive leukocyte esterase dipstick test with spontaneous bacterial peritonitis (SBP) in patients suffering from liver cirrhosis.